Deductible Status in the Pediatric Population: A Barrier to Appropriate Care?. (July 2022) - Torrecillas, Vanessa F.; Neuberger, Kaden; Ramirez, Alexander; Knighton, Andrew; Krakovitz, Paul; Richards, Nathan G.; Srivastava, Raj; Meier, Jeremy D.
Objective: The objective of this study is to evaluate the impact of high-deductible health plans on elective surgery (tonsillectomy) in the pediatric population. Study Design: Cross-sectional study. Setting: Health claims database from a third-party payer. Methods: Data were reviewed for children up to 18 years of age who underwent tonsillectomy or arm fracture repair (nonelective control) from 2016 to 2019. Incidence of surgery by health plan deductible (high, low, or government insured) and met or unmet status of deductibles were compared. Results: A total of 10, 047 tonsillectomy claims and 9903 arm fracture repair claims met inclusion and exclusion criteria. The incidence of tonsillectomy was significantly different across deductible plan types. Patients with met deductibles were more likely to undergo tonsillectomy. In patients with deductibles ≥$4000, a 1.75-fold increase in tonsillectomy was observed in those who had met their deductible as compared with those who had not. These findings were not observed in controls (nonelective arm fracture). For those with met deductibles, those with high deductibles were much more likely to undergo tonsillectomy than those with low, moderate, and government deductibles. Unmet high deductibles were least likely to undergo tonsillectomy. Conclusions: Health insurance plan type influences the incidence of pediatric elective surgery such as tonsillectomy but not procedures such as nonelective repair of arm fracture. High deductibles may discourage elective surgery for those deductibles that are unmet, risking inappropriate care of vulnerable pediatric patients. However, meeting the deductible may increase incidence, raising the question of overutilization.